From black clouds to black holes - Narlikal, Jayant V. (Singapore, WSP, 2012)
This book presents in a simple style the success story of modern astrophysics -- how the application of known physics to models of stars can, together with the observational data, help us understand what stars are made of, how they live and how they die. The account is non-technical but scientifically accurate. It is interspersed with anecdotes and analogies to make the subject matter readable and understandable even to a lay reader with some basic scientific background.
Index 199-202p.
Keywords: Astronomy; Extrasolar planets; Variable stars; Physics